Sympathetic neural inhibition of conducted vasodilatation along hamster feed arteries: complementary effects of α(1)- and α(2)-adrenoreceptor activation - Haug, Sara J (Blackwell Science Inc, 2005)
Vasodilatation initiated on arterioles of skeletal muscle ascends into the proximal feed arteries through cell-to-cell conduction along the endothelium and into smooth muscle. Whereas perivascular sympathetic nerve activity (SNA) can inhibit conducted vasodilatation and restrict muscle blood flow, the signalling events mediating this interaction are poorly defined. Therefore, using isolated pressurized (75 mmHg) feed arteries (diameter (μm) at rest = 53 ± 3; maximum = 99 ± 2; n = 86) of the hamster retractor muscle, we tested the hypothesis that distinct yet complementary signalling pathways underlie the ability of SNA to inhibit conduction. Conducted vasodilatation was initiated using ACh microiontophoresis (1 μA; 250, 500 and 1000 ms) and SNA was initiated using local field stimulation (30–50 V; 1 ms at 2, 8 and 16 Hz). With vasodilatations of 5–20 μm, conduction increased with ACh pulse duration and was inhibited progressively as the frequency of SNA increased. During SNA, conduction was partially restored with inhibition of α(1)- (0.1 μm prazosin) or α(2)- (0.1 μm RX821002) adrenoreceptors and fully restored with both antagonists present. Activating α(1)- (50 nm phenylephrine) or α(2)- (1 μm UK 14,304) adrenoreceptors inhibited conduction partially and their simultaneous activation inhibited conduction cumulatively (P < 0.05). Elevated [K(+)](o) (30 or 40 mm) or phorbol esters (0.5 μm) also inhibited conduction yet similar constriction with l-NNA (50 μm) or Bay K 8644 (10 nm) did not. Thus, the activation of α(1)- and α(2)-adrenoreceptors inhibits conducted vasodilatation through complementary signalling events. With robust coupling along the endothelium, our modelling predicts that the inhibition of conduction by SNA can be explained by reduced electrical coupling through myoendothelial gap junctions or greater current leak across smooth muscle cell membranes.